Impacto socioeconómico y cultural generados por la construcción de la carretera en pobladores de San Joaquín de Omagua, Nauta 2021 - Guimaraes Inuma, Weninger Omar (2023)
The present investigation entitled: "Socioeconomic and Cultural Impact Generated by the Construction of the Highway in the San Joaquín de Omagua Populated Center, Nauta 2021", aimed to determine the socioeconomic and cultural impact generated by the highway, the approach used was mixed, quantitative and qualitative, through surveys and interviews with 30 key actors. The main social impacts generated by the construction of the highway is the involvement of the community, the populated center and the Regional Government of Loreto in the process and the relationship with other external actors has generated encounters and disagreements as a result of power relations, there are changes in behaviors and habits as a result of the increase in migrants, which also generates changes in the possession of resources and access to spaces for their homes. At an economic level, it generated a positive impact on trade, benefiting agriculture, hunting, fishing and handicrafts, products are taken to the city of Nauta and Iquitos in less time and the means of land transport increased. Regarding cultural changes, festivities, clothing and language are no longer practiced as a result of the greater relationship with the city and the influence of globalization and the hegemonic discourse of territorial development with infrastructures of high public investment, leading to the weakening of identity community and the sense of belonging. San Joaquín de Omagua is a territory that seeks from land connectivity an opportunity to make visible its social gaps and manage initiatives for the development and well-being of its inhabitants in the Peruvian Amazon.